Deconstructing Racist Humor: How Archie Boston’s Advertisements Provoke Institutionalized Racism - Shaheila Valmai Kalyana Roeswan; Yasmine Anabel Panjaitan (OKARA: Jurnal Bahasa dan Sastra, 2021)
Humor is one of the most used mediums for overcoming the dominant power in society. One type of humor, Black Humor, was initially used by the Black community to speak their voice regarding the racism they face every day. However, it showed that even the most powerful tool could also act as a double-edged sword for its users. In this research, we analyzed three advertisements made by Archie Boston circa the 1960s that took the symbolism of the Ku Klux Klan, Uncle Sam, and slavery and turned these symbolisms into objects of humor. Using Kress and van Leeuwen’s Grammar of Visual Design, Barthes’ visual semiotics, and incongruity theory by Goldstein and McGhee, these advertisements were analyzed and then critically associated with the theory of Institutionalized Racism. The results revealed that these advertisements showed affiliation with how stereotypes are identified through symbolism by using humor and visual images. Therefore, these advertisements perpetuate negative stereotypes of the Black community by making Black people seem complicit in and supporting the racist acts that the symbols perpetuated.